Action-control mappings of interfaces in virtual reality: A study of embodied interaction - Lachmair, Martin; Fischer, Martin H.; Gerjets, Peter (Frontiers in Virtual Reality, 2022)
The development of interface technologies is driven by the goal of making interaction more positive through natural action-control mappings. In Virtual Reality (VR), the entire body is potentially involved for interaction, using such mappings with a maximum of degrees of freedom. The downside is the increase in interaction complexity, which can dramatically influence interface design. A cognitive perspective on detailed aspects of interaction patterns is lacking in common interface design guidelines, although it can be helpful to make this complexity controllable and, thus, make interaction behavior predictable. In the present study, the distinction between grounding, embodiment, and situatedness (the GES framework) is applied to organize aspects of interactions and to compare them with each other. In two experiments, zooming into or out of emotional pictures through changes of arm span was examined in VR. There are qualitatively different aspects during such an interaction: i) perceptual aspects caused by zooming are fundamental for human behavior (Grounding: closer objects appear bigger) and ii) aspects of gestures correspond to the physical characteristics of the agents (Embodiment: little distance of hands signals little or, in contrast, “creating more detail”). The GES-framework sets aspects of Grounding against aspects of Embodiment, thus allowing to predict human behavior regarding these qualitatively different aspects. For the zooming procedure, the study shows that Grounding can overrule Embodiment in interaction design. Thus, we propose GES as a cognitive framework that can help to inform interaction guidelines for user interface design in VR.